In situ fabrication and wettability of Ca2SiO4/CaTiO3 biocoating by laser cladding technology on Ti–6Al–4V alloy. (May 2013) - Yang, Y L; Guo, N
Abstract : Wetting is the first and foremost event when a biomaterial is implanted into the biological system. Hence, it is very essential to investigate the wettability of a biomaterial before further biological studies. A textured coating with different relative amounts of Ca2 SiO4 and CaTiO3 was in situ fabricated by varying laser scan speed. The wettability of different coatings was investigated. The results indicate that the relative amount of Ca2 SiO4 phase increased with decreasing laser scan speeds and reached the highest value of 48·17±2·10 mJ mm −2, and the geometrically textured topography with a surface roughness of 9·17 μm was obtained at a laser scan speed of 2 mm s −1 . The microstructure in the coating can be characterised as fine dendrites. Surface energy values varied with the relative amount of Ca2 SiO4 phase. The coating obtained at the laser scan speed of 2 mm s −1, which contains more relative amount of Ca2 SiO4, presents the highest surface energy, indicating most desirable wettability. This resulted in an increase in contact angle in simulated body fluid solution for improved wettability. The microhardness presented a gradient distribution from the coating surface (1072 HV) to the substrate (260 HV).